A review of the microbiological hazards of dairy products made from raw milk. (November 2015) - Verraes, C.; Vlaemynck, G.; Van Weyenberg, S.; De Zutter, L.; Daube, G.; Sindic, M.; Uyttendaele, M.; Herman, L.
Abstract: This review concentrates on information concerning microbiological hazards possibly present in raw milk dairy products, in particular cheese, butter, cream and buttermilk. The main microbiological hazards of raw milk cheeses (especially soft and fresh cheeses) are linked to Listeria monocytogenes, verocytotoxin-producing Escherichia coli (VTEC), Staphylococcus aureus, Salmonella and Campylobacter . L. monocytogenes, VTEC and S. aureus have been identified as microbiological hazards in raw milk butter and cream albeit to a lesser extent because of a reduced growth potential compared with cheese. In endemic areas, raw milk dairy products may also be contaminated with Brucella spp., Mycobacterium bovis and the tick-borne encephalitis virus (TBEV). Potential risks due to Coxiella burnetii and Mycobacterium avium subsp. paratuberculosis (MAP) are discussed. Pasteurisation ensures inactivation of vegetative pathogenic microorganisms, which increases the safety of products made thereof compared with dairy products made from raw milk. Several control measures from farm to fork are discussed.